Proposing an alternative model for financing micro enterprises in Afghanistan - Haqbin, Naqibullah; Mohd Thas Thaker, Mohamed Asmy; Abd Jalil, Mohamad Isa; Hamzah, Ahmad Aizuddin (Universiti Malaysia Sabah, 2023)
The advancement of Micro-Enterprises (MEs) holds significant value in a nation such as Afghanistan, where MEs form a substantial portion of the private sector and play a pivotal role in fostering the country's economic development. Notwithstanding the acknowledged significance of MEs, securing adequate financial support for them remains an onerous task. It is evident that MEs in Afghanistan confront formidable financing hurdles, encompassing exorbitant borrowing costs, stringent collateral prerequisites, rigorous documentation mandates, the necessity for comprehensive business blueprints, and the imperative need for robust financial record-keeping. Unfortunately, a considerable portion of these MEs find it difficult to meet these requisites, consequently perpetuating their challenges in procuring external financing. Consequently, this study introduces an innovative model termed the Integrated Qardhul Hasan and Equity-based Micro Enterprise Development (IQEMD) model. The study critically surveys pertinent literature related to the issues MEs encounter when attempting to secure financing, including Qardhul Hasan and equity-based financing, and utilizes these insights to formulate the IQEMD model. This model is designed not only to alleviate the external financing conundrum faced by MEs but also to enhance their overall performance and amplify their contributions to the national economic landscape. The study culminates with a prospective recommendation for further exploration in this domain.